Hubungan kepercayaan diri dengan obesitas pada siswa SMA Negeri 9 Binsus Manado - Polii, Clinton N.; Pali, Cicilia; David, Lydia (e-Biomedik, 2016)
Abstract: Obesity is a condition where there isan accumulation of excess in body fat, so the weight of a person is far above the normal condition and it is dangerous for health. Obesity or also called as overweight is a problem that is troubling among adolescents. In the group of adolescents, obesity will affect the psychosocial development including self-confidence. Appearance or ideal body shape will foster self-confidence of a person. Self-confidence is a belief of a person that he or she is able to behave as needed to obtain the expected results. This study aims to look at the relationship level of confidence with obesity of the students at SMA Negeri 9 Binsus Manado. This study is using correlational method with cross sectional design. The results showed the level of self confidence for adolescent who has obesity in the highest category are 31 people (47.6%). Results on the result r = -0.224 and p = 0.080. Conclusion: This study shows the significant value 0.383, since the sig value is more than 0.05, then H0 is accepted. It means that there is no significant relationship between obesity and self confidence in SMAN 9 Binsus ManadoKeywords: obesity, confidence.Â Abstrak: Obesitas adalah suatu keadaan dimana terjadi penumpukan lemak tubuh yang berlebih, sehingga berat badan seseorang jauh di atas normal dan dapat membahayakan kesehatan. Obesitas atau disebut juga kegemukan, merupakan suatu masalah yang cukup merisaukan dikalangan remaja. Pada kelompok remaja, obesitas akan berpengaruh pada perkembangan psikososial termasuk kepercayaan diri. Penampilan atau bentuk tubuh yang ideal akan menumbuhkan rasa percaya diri seseorang. Kepercayaan diri merupakan suatu keyakinan yang dimiliki seseorang bahwa dirinya mampu berperilaku seperti yang dibutuhkan untuk memperoleh hasil seperti yang diharapkan. Penelitian ini bertujuan untuk melihat hubungan tingkat kepercayaan diri dengan obesitas pada siswa di SMA Negeri 9 Binsus Manado. Penelitian ini bersifat korelasional dengan rancangan potong lintang. hasil penelitian menunjukkan tingkat kerpecayaan diri pada remaja yang obesitas berada pada kategori tinggi sebanyak 31 orang (47,6%). Hasil analisis data diperoleh hasil r= -0,224 dan p= 0,080. Simpulan: Penelitian ini menunjukkan nilai signifikasi 0,383, dimana nilai sig lebih dari 0,05 maka H0 diterima. Hal ini berarti tidak terdapat hubungan yang signifikan antara obesitas dan kepercayaan diri di SMAN 9 Binsus Manado. Kata kunci: obesitas, kepercayaan diri.